A Sociolinguistics Analysis Of Fashion Register In Cosmo Girl Magazine - Krisnawati, Noka Leoni; , Drs. Maryadi, M.A; , Dra. Siti Zuhriah, M. Hum (2013)
This research analyzes of fashion register in Cosmo Girl magazine. The major problem in this study are to know the linguistics form and the meaning of fashion register in Cosmo Girl magazine. The type of this research is descriptive qualitative research. The object of this research is the fashion register in Cosmo Girl magazine. The data are register words and phrases of fashion in Cosmo Girl magazine January 2013 edition. In collecting data, the writer searching Cosmo Girl magazine from the book store, reading the Cosmo Girl magazine and try to find some word and phrases that belong to the fashion register, writing the register words and phrase, and coding the data. In analyzing the data, the researcher classifies the data which can be categories as fashion register, analyes the linguistics form and meaning, analyzes context of situation, identifies the differences between lexical and contextual meaning and draw conclusion. Based on the data analysis, the researcher finds that there are the linguistics form4 data of noun, 1 datum of verb, 5 data of adjective, 2 data of compound word, 16 data of noun phrase and 3 data of adjective phrase. Based on the meaning the researcher finds 23 data in contextual meaning and 8 data in lexical meaning.